Stimulating effect of Streptococcus faecalis on phagocytosis in gnotobiotic piglets - Mandel, L; Talafantová, M; Trebichavský, I; Trávnícek, J (Folia microbiologica, 1989)
The concentration of active phagocytes in peripheral blood remained in germfree pigs up to the age of one year approximately at the same level as found at the age of 7 d and did not exceed 0.3 X 10(9)/L of blood, whereas a steady increase was established in conventional pigs. Monoassociation of gnotobiotic piglets with Streptococcus faecalis increased during 24 h the concentration of circulating granulocytes and the concentration of active phagocytes. An even more pronounced effect was obtained when formolized S. faecalis cells were applied intraperitoneally to germfree piglets. This treatment elevated the phagocytosis index also in conventional piglets, as well as in germfree piglets previously given cyclophosphamide. Escherichia coli O 83 or a mixture of anaerobic bacteria did not cause any serious changes in the activity of phagocytosis in gnotobiotic piglets. S. faecalis seems to be a natural factor stimulating both the release of granulocytes from their depots as well as their phagocytic activity.
Keywords: Animals; gnotobiologické modely; novorozená zvířata; Swine, Miniature; Animals, Newborn; počet leukocytů; miniaturní prasata; monocyty; prasata; Leukocyte Count; Germ-Free Life; Monocytes; Swine; Neutrophils; fagocytóza; Phagocytosis; neutrofily; Enterococcus faecalis; zvířata